Demand and Supply Issue (2008-2009) (The Pakistan Development Review, 2008)
In 1994 our major source of power was hydel. Cost of hydel is only in the beginning which includes construction of dam and water reservoir. It is the cheapest source with no input cost and very low administrative cost .It is the best natural way of producing energy. No noise, no pollution and many associated benefits. This source cost wapda less than Rs1 per unit. In 1994 IPPs came into action using thermal power generators running on diesel. After purchasing electricity from IPPs the purchase price of Wapda increased up to Rs 6 and 12 per unit depending on the deals with different IPPs. This method proved to be very costly and full of pollution. Due to price hike of diesel in the past, the input cost (cost of diesel) increased by many fold. So the economy was hit and the balance of payment was disturbed badly. Actually this method was meant for short term solution. But due to political instability we lost our sight from the real scene and based our future energy plan on a very costly method. Why? Answer is, as a nation including politicians, bureaucrats, policy makers and everybody enjoy their present leaving and passing these queries, fears and problems to the next generation hoping that all will be well. More than 35 years past away and no concrete solution appeared. But the people of Pakistan specially our new generation are facing this bitter truth i.e., load shedding We have lost rather wasted our precious 35 years. We cannot makeup this gap. Whenever we will try to make a deal with the foreign investors regarding any power generation project, it will always be unfair. unfair why? Because, when somebody knows that you are dying for what he has, he will blackmail you and make u go his way. This is called business. We have lost both the time and competitiveness. If we go on making deals with IPPs now known as “Rental power houses” which will provide us electricity as high as Rs19 per unit. We will lose a lot in all fields. Such as: